KESULITAN SISWA DALAM MEMECAHKAN MASALAH PADA MATERI GELOMBANG MEKANIK - Samria; Supriyatman (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
This study aims to determine the difficulties and factors that cause class XII students of MAN Insan Cendekia Palu City in solving physics problems on mechanical wave material. This type of research is qualitative research. The subjects in this study were 25 students of class XII MAN Insan Cendekia Palu City. The determination of 6 respondents was chosen based on the students' ability to solve physics problems on the material of mechanical waves. The scores obtained are grouped into high category, medium category, and low category. Classification of categories based on the calculation of the average value and standard deviation. The average value obtained is 29.52 and the standard deviation is 14.51. Data collection was obtained from problem solving difficulty tests and interviews. The results obtained are that in stage 1 all respondents experienced difficulties, at stages 2, 4, and 5 generally respondents experienced difficulties, in stage 3 most respondents experienced difficulties. The factors that cause students difficulty in terms of each stage of Heller are respondents who do not understand the questions and cannot change from verbal sentences to pictures or sketches, respondents are less careful in reading questions and do not remember symbols and teachers only focus on solving questions, respondents are confused in determining the equation, respondents are less careful in arithmetic operations and confusion in the process, respondents are not accustomed to checking their answers and lack of time when solving questions, respondents do not re-learn class XI material, especially mechanical wave material, as a result respondents do not remember the material and most of the respondents wrong in solving calculation problems.